Grain yield losses in wheat from the seed gall nematode Anguina tritici under field conditions - Tulek, Adnan; Ozturk, İrfan; Tulek, Banu; Goktepe, Onur; Salah-Eddine Laasli; Lahlali, Rachid; Dababat, Abdelfattah A. (Wiley, 2024)
The effects of the seed gall nematode ‘Anguina tritici’ (Steinbuch, 1799) on the agronomic characteristics of some bread wheat cultivars were investigated at the Trakya Agricultural Research Institute, Türkiye. An experiment was carried out in two different locations in Edirne in the 2019–2020 growing season. A total of 19 winter bread wheat cultivars were evaluated to assess infected grain number, healthy grain number, infected grain rate and yield. According to the results of the combined variance analysis, a statistically significant difference (p ≤ .01) was found in terms of yield from the application of inoculum. Compared to the control in wheat cultivars, there was a 52.15% decrease in the yield of infected parcels due to the damage of wheat seed gall nematode. The highest yield loss in infected parcels occurred in cv. Damla with 64.22% loss, while the least yield loss occurred in cv. Yüksel cultivar with 19%. Pathological symptoms, curling and twisting of the leaves, were not observed on green plants of cv. Yüksel cultivated in the field.